US Latin America policy under Trump. Issue 2 (7th February 2017) - Unknown
Abstract : Trump's Latin America policy, so far generally subdued, may become more active. The administration has sharply antagonised Mexico with harsh immigration and trade policies. Trump also appears inclined to take strong positions on Cuba and Venezuela, and his tilt against trade agreements could present strategic opportunities for China in the region.